THE EFFECT OF BRAND EQUITY ON BRAND TRUST WITH BRAND REPUTATION AS A MEDIATING VARIABLE (STUDY ON COSTUMERS OF SATE KMS IN PADANG CITY) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2020)
This study aims to determine the effect of Brand Equity on Brand Trust through Brand Reputation as a mediating variable (Study on costumers of Sate KMS in Padang City). This research is explanatory with quantitative methods. The sampling technique used in this study was purposive sampling for consumers who had bought and consumed KMS sate Padang, with a sample of 125 respondents. This study uses Partial Least Square with the SmartPLS 3.0 program. The results of this study indicate that food & service quality, brand affect, brand awareness, and brand association have a significant effect on brand trust with a brand reputation as a mediating variable.Keywords: brand equity, brand reputation, brand trust